Respiratory depression effects of diazepam, midazolam premedication and thiopental-isoflurane combination anaesthesia in water buffaloes (Bubalis bubalis) - Singh, Harmanjeet; Singh, Tarunbir; Verma, Pallavi; Mohindroo, Jitender; Raghunath, Mulinti; Saini, Narinder Singh; Singh, Navdeep (Buffalo Bulletin, 2021)
Study was designed to evaluate respiratory depression and blood gas, acid base and electrolyte changes in twelve water buffaloes subjected to general anaesthesia while performing diaphragmatic herniorrhaphy in dorsal recumbency. Animals were randomly divided into two groups comprising of six animals each. Anaesthetic protocol included midazolam (Group I) and diazepam (Group II) preanaesthesia 0.2 mg/kg bwt. followed by induction with thiopental and maintenance with isoflurane in both the groups. Estimation of blood gas, acid base and electrolyte values showed no major alterations in blood electrolyte (Sodium, Potassium, Chloride) values in both groups. However, the electrolyte values were better maintained in animals subjected to midazolam preanaesthesia (Group II). Blood gas and acid base values in two groups showed significant decrease in blood pH, PaO2 and increase in PaCO2 during the anaesthesia indicating respiratory acidosis. It was observed that respiratory acidosis was the predominant acid base alteration in animals subjected to general anaesthesia owing to dorsal recumbency and depressed respiration.